2022
DOI: 10.3390/ijerph192416512
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Increases MMP-12 and MBP Concentrations after Coronary Artery Bypass Graft Surgery with Extracorporeal Circulation Anaesthesia without Impacting Cognitive Function: A Randomised Control Trial

Abstract: Postoperative neurological deficits remain a concern for patients undergoing cardiac surgeries. Even minor injuries can lead to neurocognitive decline (i.e., postoperative cognitive dysfunction). Dexmedetomidine may be beneficial given its reported neuroprotective effect. We aimed to investigate the effects of dexmedetomidine on brain injury during cardiac surgery anaesthesia. This prospective observational study analysed data for 46 patients who underwent coronary artery bypass graft surgery with extracorpore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…Similarly, another single-blinded, prospective, randomized controlled trial in 183 elder patients 60 years or older undergoing cardiac surgery, of which 91 patients in the dexmedetomidine group and others received propofol, demonstrated that this sedative agent compared to propofol reduced the incidence (17.5% compared to 31.5%), delayed onset (day 2 versus day 1), and shortened duration of POD (2 days versus 3 days) [52]. Moreover, the participation of 46 patients who underwent coronary artery bypass graft surgery participated in a randomized controlled trial, suggested that dexmedetomidine compared to typical anesthesia could increase the levels of neural protective biomarkers including matrix metalloproteinase-12 and myelin basic protein [53]. However, a higher rate of hypotension was reported as an adverse effect of dexmedetomidine administration requiring further studies to elucidate other possible side effects [51].…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…Similarly, another single-blinded, prospective, randomized controlled trial in 183 elder patients 60 years or older undergoing cardiac surgery, of which 91 patients in the dexmedetomidine group and others received propofol, demonstrated that this sedative agent compared to propofol reduced the incidence (17.5% compared to 31.5%), delayed onset (day 2 versus day 1), and shortened duration of POD (2 days versus 3 days) [52]. Moreover, the participation of 46 patients who underwent coronary artery bypass graft surgery participated in a randomized controlled trial, suggested that dexmedetomidine compared to typical anesthesia could increase the levels of neural protective biomarkers including matrix metalloproteinase-12 and myelin basic protein [53]. However, a higher rate of hypotension was reported as an adverse effect of dexmedetomidine administration requiring further studies to elucidate other possible side effects [51].…”
Section: Pharmacological Interventionsmentioning
confidence: 99%